Impact of clinical practicals on the mental health status of university nursing students - Gaoses, Stephanie L.; Amakali-Nauiseb, Taimi; Ndafenongo, Sesilia (International Journal Of Community Medicine And Public Health, 2023)
Background: Mental health has been slightly neglected in all aspects of life. The aim of the study was to explore the impact of clinical practicals on the mental health status of 4th year nursing degree students at the University of Namibia main campus. The objective of the study was to explore the impact of clinical practicals on the mental status and describe the general attitude of 4th year nursing degree students at the University of Namibia main campus towards clinical practicals. Methods: A cross-sectional, explanatory research study with a qualitative approach was employed. The participants were among 104, fourth year 2021 nursing degree students at the University of Namibia main campus. Virtual interviews were conducted via Microsoft teams until saturation point was reached, the thematic/grounded theory was used to establish themes from the context. Results: Clinical practicals have an impact on the mental health status of fourth year nursing degree students at the University of Namibia main campus. The students experience slightly negative attitude towards clinical practicals due to immense requirements and limited time to complete them. Conclusions: The School of Nursing and Public Health at the University of Namibia have to provide professional services to cater for the mental health status of students such as a counsellor, social worker, psychologist, conducive environment or management skills to help students to cope. In addition, this is thought to also improve the attitude of students towards clinical practicals, in producing- effective and efficient students.